2008
DOI: 10.1080/08860220801964210
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Depot Oral Cholecalciferol Treatment on Secondary Hyperparathyroidism in Stage 3 and Stage 4 Chronic Kidney Diseases Patients

Abstract: By the time patients require dialysis replacement therapy, nearly all chronic kidney diseases (CKD) patients are affected with uremic bone diseases. High-turnover osteodystrophy can be prevented; patients with CKD should be monitored for imbalances in calcidiol (25 OH vitamin D), calcium, and phosphate homeostasis. We aimed to determine the effect of a monthly oral 300,000 IU vitamin D 3 (cholecalciferol) supplementation on the uremic bone diseases (UBD) markers such as iPTH and alkaline phosphatase in CKD pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 9 publications
3
31
0
1
Order By: Relevance
“…The combined search of MEDLINE, SCOPUS, and nephrology conference proceedings identified 3846 citations, of which 3701 were excluded after title and abstract review. Full-text assessment of 145 potentially relevant articles identified 22 studies (5 RCTs [see references [23][24][25][26][27] and 17 observational studies [see references 19,20,28 -42]) enrolling 1593 patients. Nine of the 11 authors who were contacted for additional data or clarification responded.…”
Section: Search Resultsmentioning
confidence: 99%
“…The combined search of MEDLINE, SCOPUS, and nephrology conference proceedings identified 3846 citations, of which 3701 were excluded after title and abstract review. Full-text assessment of 145 potentially relevant articles identified 22 studies (5 RCTs [see references [23][24][25][26][27] and 17 observational studies [see references 19,20,28 -42]) enrolling 1593 patients. Nine of the 11 authors who were contacted for additional data or clarification responded.…”
Section: Search Resultsmentioning
confidence: 99%
“…Similarly, Kovesdy et al found no benefit for control of PTH with ergocalciferol in patients with stages 3-4 CKD (26). In contrast, Dogan et al found that large 300,000 IU bolus of cholecalciferol significantly reduced PTH in stages 3-4 CKD (versus no intervention), but follow-up was limited to 1 month (27). A larger study by Oksa et al compared 5000 IU versus 20,000 IU of cholecalciferol and found the larger dose was more effective in suppressing PTH, but this study included CKD stages as early as 2-4 (28).…”
Section: Hospitalizations and Deathmentioning
confidence: 99%
“…Researchers have shown that increasing serum 25(OH) D concentrations by administration of cholecalciferol can reduce serum PTH levels (20)(21)(22)(23). However, Kovesdy et al believes inactive vitamin D cannot reduce PTH levels (24).…”
Section: Discussionmentioning
confidence: 99%